Graphene/N-doped carbon sandwiched nanosheets with ultrahigh nitrogen doping for boosting lithium-ion batteries. Issue 4 (11th January 2016) - Liu, Xianghong; Zhang, Jun; Guo, Shaojun; Pinna, Nicola
Abstract : N-doped carbon/reduced graphene oxide nanosheets with a high N-doping of 15.4% exhibit high reversible capacity, superior cycling life and good rate capability for lithium-ion batteries. Abstract : Enhancing the nitrogen (N) doping in carbon nanomaterials has been suggested as an effective approach to enhance the performance of lithium ion batteries (LIBs). However, achieving N-doped carbon nanomaterials with an ultrahigh N content is still a great challenge, thus limiting the capacity enhancement. Herein, we demonstrate a new procedure for the synthesis of unique sandwich architecture of N-doped carbon/reduced graphene oxide (N-carbon/rGO) derived from simple pyrolysis of a polypyrrole/GO nanosheet precursor. The N-carbon/rGO exhibits the highest N-doping of 15.4% reported in all the carbon-based nanomaterials, and a high specific surface area of 327 m 2 g −1 with a micro/mesoporous structure. They combine the advantages of high conductivity of rGO, very high N-functionalities, and the porous structure of carbons, which endow them with appealing electrochemical lithium storage properties with a high initial reversible capacity of 1100 mA h g −1 at 100 mA g −1, excellent rate capability up to 20 A g −1, and superior cycling stability over 1000 cycles at a high current density of 1 A g −1 . The present work highlights the important role of tuning the nitrogen doping in enhancing the performance of LIBs.